Legal Hybridity in Hong Kong and Macau - Castellucci, Ignazio (McGill Law Journal / Revue de droit de McGill, 2012)
The article aims to compare the case of the two Chinese Special Administrative Regions (SARs) of Hong Kong and Macau against the theoretical grid developed by Vernon V. Palmer to describe the “classical” civil law-common law mixed jurisdictions. The results of the research include an acknowledgement of the progressive hybridization of the legal systems of Hong Kong and Macau, hailing from the English common law and the Portuguese civil law tradition, respectively, by infiltration of legal models and ideologies from Mainland China.The research also leads to a critical revision and refinement of the methodology and tools developed by Palmer in order to make them applicable to a wider range of processes of legal hybridization beyond “classical” mixes, and to a better appreciation of how transitional political and institutional phases play a critical role inlegal “mixity” or hybridity.